Genetically Modified Foods: Main Market Actors´ Perspectives - КараеваОльга Сергеевна; КамальдиноваЛидия Рафаильевна (Journal of Economic Sociology, 2011)
The article considers the emergence of genetically modified foods and practices of labeling goods as «nonGM» and defines it as a critical situation in the history of consumer market. Introduction of products produced with the use of genetic engineering technology into mass consumption is a contradictory process because the effects of GM-components on human health have not been fully recognized up to now. Therefore, the views of leading market sellers regarding the penetration of genetically modified foods and its potential consequences are especially interesting. The paper is based on 8 in-depth interviews with producers, series of expert interviews with physicians, and a standardized survey of Moscow residents. Economic theory of conventions is applied to resolve the task.